Uma avaliação da participação do fator de relaxamento endotelio-dependente (EDRF) e do fator de ativação de plaquetas (PAF) no escape vascular e na taquifilaxia do rim isolado de coelho - Ferreira, Maria Guimaraes (1989)
The participation of EDRF and PAF in the mecha- nism of the vascular escape and tachyphylaxis was evaluated using rabbit kidneys, isolated and perfused with Krebs- Henseleit solution. The kidneys were compared with organs infused with EDRF blockers agents (methylene blue, colage- nase and EP 10161), etherphosphòlipids(PAF and Lyso - PAF) and PAF antagonists (naturally Qccuring products derived from Ginkgo biloba tree and synthetic compounds, 48740 RP and WEB 2086). The study of renal reactivity showed that kidneys perfused with Lyso - PAF, an isomer of PAF devoided of phar macological activity, were able to enchance vascular escape reactions. PAF exogenous otherwise7 did not change any parameter of renal function. EP 10161, a lipooxigenase inhibitor, was able to promote a late, but significant reduction on escape reactions . The PAF antogonists, ginkgolides B,C and J, with different PAF binding activities were used in order to confirm PAF participation on vascular escape and phylaxis of renal artery bed. The ginkgolide B (BN promoted a partial blockade of tachyphylaxis and a tachy52021) , aignifi cant reduction of escape reactions in the second period of norepinephrinae infusion.Ginkgolíde. J, (BN 52024) , which has the weaker PAF antagonistic activity, was able to block completely the vascular escape and tachyphylaxis indu ced by norepinephrine. From these studies we concluded that PAF parti- cipates in the mecanism of vascular escape reactions through the results obtained from its precursor, Lyso-PAF. The effects of BN 52024 on the vascular escape and tachyphylaxis. were characterized by complete blockade of the vasoative phenonena. This result may also be attri- buted to an unique property of this class of compounds,which could exert a specific action on intracellular calcium de- posits, making possible the blockade of tachyphylaxis.